Pulmonary atresia with ventricular septal defect and tetralogy of Fallot: transannular path augmentation versus systemic to pulmonary artery shunt for first-stage palliation. (18th November 2020) - Lenoir, Marien; Fouilloux, Virginie; Desnous, Beatrice; Rahmani, Bilal; El Gueddari, Nabila; Ovaert, Caroline; Aries, Edouard; El Louali, Fedoua; Aldebert, Philippe; Metras, Dominique; Macé, Loic
Abstract: Background: Pulmonary atresia with ventricular septal defect and severe tetralogy of Fallot require a palliative procedure for pulmonary artery rehabilitation. For first-stage palliation, two main surgical options are still debated: right ventricle to pulmonary artery connection and modified Blalock–Taussig shunt. We compared the clinical outcomes of the two procedures. Methods: From 1995 to 2018, 88 patients needed palliation (pulmonary atresia with ventricular septal defect n = 47; tetralogy of Fallot n = 41). Among these patients, 70 modified Blalock–Taussig shunt and 18 transannular path augmentation were performed before 6 months of age. Using a 1:1 propensity score match analysis, 20 patients were included in the analysis. The primary outcome was in-hospital mortality and pulmonary artery growth. Results: After matching, the pre-operative Nakata was smaller in transannular path augmentation 54 ± 24 mm 2 /m 2 than modified Blalock–Taussig shunt 109 ± 31 mm 2 /m 2 (p < 0.001). The age and weight were similar (p = 0.31 and p = 0.9, respectively). There was no difference in in-hospital mortality (p = 0.3). The Nakata index before biventricular repair and delta Nakata were smaller in modified Blalock–Taussig shunt group (206 ± 80 mm 2 /m 2, 75 ± 103 mm 2 /m 2 ) than transannular path augmentation (365 ± 170 mm 2 /m 2, 214 ± 165 mm 2 /m 2 ; p = 0.03; p < 0.001). Median time to biventricular repair was similar (p = 0.46). The rate of interstage reintervention was similar (p = 0.63). Conclusions: The transannular path augmentation is better for the rehabilitation of the native pulmonary artery. Despite a smaller pulmonary artery, right ventricle to pulmonary artery connection is equivalent to modified Blalock–Taussig shunt for rate of biventricular repair and time to biventricular repair.